Improving the efficiency of steam-turbine plants of different capacities - Шубенко, Олександр Леонідович; Сенецький, Олександр Володимирович; Бабенко, Ольга Анатоліївна (Eastern-European Journal of Enterprise Technologies, 2014)
Important scientific and technical problem of increasing operational efficiency of steam-turbine plants by developing new technologies for solving problems of efficient distribution of thermal and electrical loads between turbines and network heaters of cogeneration turbines during the heating period is solved in the paper. The scientific principles and methods for solving problems of both the analysis of power plant states, and their synthesis (optimization), taking into account a large number of factors, affecting the indicators of thermal circuit elements in their interaction, thus providing modeling of energy systems of different configurations with the ability to include new elements are developed. Additional modules of mathematical model and software-computer complex for calculating thermal circuits to implement energy-saving measures are developed and introduced. Formulation and solution of the problem of determining rational operation modes of thermal circuits of low-capacity steam-turbine plants (confirmed by implementation acts) is first performed. For power units of industrial enterprises, expediency of building steam-turbine plants up the power steam boilers (confirmed by implementation acts) is shown. The optimum modes of heat output from cogeneration turbines T-100/120-130 and T-250/300-240 (confirmed by implementation acts) are determined. The obtained results have shown the feasibility of solving the energy-saving optimization problems through generating additional electric power from CHP turbine plants. To solve this problem, new methods, which allow to propose measures on saving fuel and energy resources without additional capital investment, are used.